INDONESIA ISLAMIC BANK MERGER: STAGES, CHALLENGES, AND STRATEGIES - mutmainah; Citra Sukmadilaga; Prima Yusi Sari (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2022)
This study analyzes the Indonesia Islamic Bank (BSI) merger's stages, challenges, and strategies. The type of data is quantitative. The research method used is the Literature review method. The data used is secondary data in the form of journal articles used for publication in 2014-2021. The results showed that the stages during the Indonesia Islamic Bank (BSI) merger process started from the approval of the BRIS, BNIS, and BSM Board of Commissioners on the Merger Plan on October 20, 2020, until it officially started operating on February 1, 2021. In addition, the challenge for the Indonesia Islamic Bank (BSI) merger is the market share of the Islamic finance industry, which is still small or lagging compared to conventional banks. Thus, several strategies can be carried out by Indonesia Islamic Bank (BSI), starting from improving business processes, strengthening risk management, strengthening human resources (HR), in enhancing digital technology. The results of this study are expected to be input for Indonesian Islamic banks in particular to be able to determine the right strategy in dealing with mergers so that they can be a solution to the challenges that will be faced by Indonesian Islamic banks. In addition, the government, namely the Financial Services Authority (OJK) can coordinate with the Sharia Accounting Standards Board (DSAS) and the Indonesian Ulema Council (MUI) to supervise and assist in accelerating the development of Islamic banking.